Ligand effects on the optical and chiroptical properties of the thiolated Au18cluster. - ALFREDO TLAHUICE FLORES (Royal Society of Chemistry, 2016)
The effect of chiral and achiral ligands protecting the inner Au9 core of the Au18(SR)14 cluster is studied based on density functional theory (DFT) and its corrected long-range interaction (DFT-D) approach. It was found that the electronic properties (energy levels) depend on the specific ligands, which induce distinct distortions on the Au–S framework. However, the substitution of S-c-C6H11 as SCH3 ligands may be considered to be correct given the obtained resemblance to the displayed bonding, optical and chiroptical properties. A further comparison of the CD and UV spectra displayed by the Au18 cluster protected by chiral and achiral ligands attests that more intense profiles are featured by ligands including phenyl rings and/or oxygen atoms such that the Au18 cluster protected by either achiral metamercaptobenzoic acid (m-MBA) or achiral SPh ligands displays more intense UV and CD signals. These results provide new insight into the effect of ligands on thiolated gold clusters.